Maturity Level and Technical Challenges of Digital Public Service Systems: Tingkat Kematangan dan Tantangan Teknis Sistem Layanan Publik Digital - Verizza Rizky Pribadi (Academia Open, 2025)
General Background: Digital transformation in public services is a national priority in Indonesia, operationalized through the Electronic-Based Government System (SPBE). Specific Background: The City of Malang launched the SiApel platform to improve administrative services; however, its implementation faces challenges such as low public engagement and unresolved technical issues. Knowledge Gap: Despite the growing adoption of local digital platforms, existing research lacks a comprehensive maturity assessment framework that integrates SPBE policy, user-centric service quality indicators, and public sector innovation models. Aims: This study evaluates the maturity level of the SiApel platform using SPBE standards and PermenPANRB No. 14 of 2017, while identifying technical and non-technical implementation barriers through the Public Sector Process Rebuilding (PPR) Model. Results: Findings reveal that SiApel is in a transitional maturity stage, with key deficiencies in system interoperability, user interface design, and real-time user support. Novelty: The study introduces a holistic evaluation model that integrates regulatory benchmarks, service quality metrics, and user-centered digital design principles to assess local e-government platforms.Implications: To advance SPBE goals, the study emphasizes the need for institutional readiness, human resource development, and inclusive digital service design. Enhancing technical capabilities and aligning services with citizen needs are essential for delivering effective, user-centered public services. Highlights: Assesses e-government maturity using SPBE and PermenPANRB standards. Identifies technical and non-technical barriers to SiApel’s adoption. Proposes an integrated evaluation model for local digital services. Keywords: Digital Transformation, E-Government, SPBE, Public Service Innovation, SiApel Platform